Perceptions, attitudes and beliefs on antenatal exercises among primiparous pregnant women: a qualitative study in Sri Lanka - Sepalage Nilanthi Chathurika; Chathura Rathnayake; Deepika Indumathie Nanayakkara; Sampath Udaya Bandara Thennakoon; Abey Rathnayake (BMJ Open)
Background Even if promoting antenatal exercises is an evolving concept worldwide, there is a scarcity of qualitative exploratory studies which directly focus on pregnant mothers’ views about exercises. So, this study was designed to (1) explore pregnant women’s perceptions, attitudes and beliefs about antenatal exercises, and (2) provide significant annotations prior to constituting interventions for antenatal exercises.Methods A qualitative survey was carried out with 19 primiparous pregnant women using stratified purposive sampling at the antenatal clinic, in a tertiary care hospital, Sri Lanka. In-depth interviews were conducted through a predesigned, semistructured interview guide from January to April 2021. Data were transcribed, examined and organised, then subjected to thematic analysis using inductive approach.Results Most of the pregnant women described numerous benefits and had optimistic views on exercises. However, the absence of a comprehensive understanding on the impact of exercise on a healthy pregnancy is apparent, primarily caused by a dearth of health education and reliable information sources. Also, they were unlikely to initiate exercises in their pregnancy period due to a lack of guidance through the antenatal clinic and/or health professionals. Concerning beliefs, main stream-believed exercises provide assistance for normal labour process and exercises advantageous in both antenatal and post-partum periods. Besides, few of them restricted their conversations on the drawbacks of exercises by illuminating erroneous beliefs.Conclusions The majority of participants realised the importance of exercises and had positive attitudes while the minority presenting misconceptions. The need for healthcare providers’ support and guidance is highly anticipated by pregnant women to engage in antenatal exercises.